Soil resilience in agricultural systems in the Calimaya municipality - García-Fajardo , Belina; Nava-Bernal, Gabino; Alvarez-Arteaga, Gustavo; Franco-Maass, Sergio (Ecosistemas y Recursos Agropecuarios, 2024)
The rainfed agriculture of the State of Mexico presents physical and chemical degradation processes that affect soil's quality. The objective was to analyze the resilience of agricultural soils in the presence of these processes in the production of maize and potato, in the municipality of Calimaya, State of Mexico. The methodology integrates the evaluation of soil quality through physical and chemical indicators. Three patterns were identified: two of rainfed maize systems and one of potato. The degradative processes derived from agricultural management decrease the quality of the soils in the area, translated into the loss of structure and porosity and the availability of nutrients. It was identified that the low rating of soil indicators affects its short-term resilience, which is supported by the inclusion of external inputs and incipient empirical practices that maintain agricultural production profitability.
Keywords: Soil Quality